GAMBARAN TINGKAT PENGETAHUAN ANAK TENTANG KARIES GIGI DI DESA BEBANDEM WILAYAH KERJA PUSKESMAS BEBANDEM: DESCRIPTION OF CHILDREN KNOWLEDGE LEVEL OF DENTAL CARIES IN PUSKESMAS (HEALTH CENTER) OF BEBANDEM VILLAGE. - Suartini, Ni Putu; Asdiwinata, I Nyoman; Purwanti, Ika Setya (Bali Medika Jurnal, 2019)
Everyone can experience dental caries, generally school-age children throughout the world estimated 90% had experienced caries. Bebandem Health Center, 2018 the incidence of dental caries in elementary school students in Bebandem is quite high, namely 587 students experienced dental caries. The purpose of this study is to know description of children level of knowledge about dental caries. This stuy used 287 respondent. The results of the validity and reliability test are the value of crombach’s alpha > constant value (0,958>0,7) In this research obtained characteristics of children knowledge of dental caries in large part respondents were in female sex as many as 152 children (53.0%) and many men 135 children (47,0%), based on age shows the majority of respondents were at the age of 9 years 80 children (27.9%) and 11 years as many as 80 children (27.9, based on class shows the majority of respondents are in class V as many as 78 children (27.2%), and based on dental caries shows the majority of respondents did not experience caries cavities as many as 183 children (63.8%). The level of children knowledge about caries the teeth of most respondents had a sufficient level of knowledge of 181 children (63.7%). The prevalence of dental caries in children is mostly the type 57 female children (19.9%) experienced dental caries, the highest number who experienced dental caries at the age of 9 as many as 40 children (13.9%). The results of this safekeeping can add insight to children about dental caries and know more about dental caries or cavities.